PENGEMBANGAN PERANGKAT PEMBELAJARAN PENDIDIKAN KEAKSARAAN DASAR BERBASIS KEARIFAN LOKAL PADA KOMUNITAS ADAT TERPENCIL (KAT) SUKU DAYAK MERATUS - Nurazizah, Nunung (JIV-Jurnal Ilmiah Visi, 2018)
The learning instruments that consisted of the teaching materials, syllabuses, lesson plans (RPP), learning guides, and evaluation guides of basic literacy educational learning at the remote indigenous community of Dayak Meratus tribe were composed for the completion of the basic literacy educational learning instruments in order to achieve course learning outcome of the basic literacy education in accordance to the regulation of the minister of education and culture no.86 2014. The research and development method was employed in developing the learning instruments. The tryouts in this research and development were conducted in PKBM Belimbing of Hulu Sungai Selatan (as the experiment group) and SPNF SKB Balangan (as the control group) from August to October 2017. The basic literacy educational learning instruments conceptual product validity test was obtained with the mean calculation of 82.8% which meant that validity level was very high. The attractiveness and conceptual literacy test was obtained with the mean calculation of 76,4% which meant that the attractiveness level was in the high category. The effect of the learning instruments’ implementation was intended that the learners could get the literacy in all aspects of their life. References Arsyad, A. (2003). Media pembelajaran. Jakarta: Raja Grafindo. Badan Pusat Statistik. (2016). Survei sosial ekonomi nasional tahun 2016. Diakses dari https://microdata.bps.go.id/mikrodata/index.php/catalog/SUSENAS Borg, W. R., & Gall, M.D. (1979). Educational research, an Introduction 3 ed. New York: Longman. Dinas Kependudukan dan Catatan Sipil Kabupaten Hulu Sungai Selatan. (2013). Data kependudukan. Diakses dari http://dukcatpil.hulusungaiselatankab.go.id/ Dinas Pendidikan Kabupaten Balangan. (2017). Data buta aksara tahun 2017. Diakses dari http://www.balangankab.go.id/?set=viewBk&flag_template2=1&flag=1&page=1&id=473 Dinas Pendidikan Kabupaten Hulu Sungai Selatan. (2016). Data buta aksara tahun 2016. Diakses dari http://disdik.hulusungaiselatankab.go.id/ Ella, Y. (2016). Tahun 2030 seluruh anak peroleh akses pendidikan pra-SD. Diakses dari https://www.kemdikbud.go.id/main/blog/2016/02/tahun-2030-seluruh-anak-peroleh-aksespendidikan-prasd Faidi, A. (2015). Suku dayak suku terbesar dan tertua di Kalimantan. Makassar: Arus Timur. Kalimantan Pos. (2016). Sambutan Gubernur Kalimantan Selatan pada Hari Aksara Internasional tahun 2016. Diakses dari http://pauddikmaskalsel.kemdikbud.go.id/index.php/berita-bp-paudni/496-upacaraperingatan-hari-aksara-internasional-provinsikalimantan-selatan Peraturan Menteri Pendidikan dan Kebudayaan Republik Indonesia Nomor 86 tahun 2014 tentang Penyelenggaraan Pendidikan Keaksaraan Dasar Peraturan Menteri Dalam Negeri Nomor 39 Tahun 2007 tentang Pedoman Fasilitasi Ormas Bidang Budaya, Keraton dan Lemadat Subdit Pendidikan Keaksaraan. (2005). Bahan ajar keaksaraan. Jakarta: Direktorat Pendidikan Masyarakat. Syahriansyah, dkk. (2011). Upacara adat dayak dan banjar Kalimantan Selatan. Banjarmasin: Antasari Press.